Profiles of primary brain abscesses and their impact on survival: An international ID-IRI study - Şahin, Meyha; Mert, Ali; Emecen, Ahmet Naci; Strunjas, Natalija Planinc; Fasanekova, Lenka; Batırel, Ayşe; Erdem, Hakan (My University, 2024)
Objectives: This study of 331 primary brain abscess (PBA) patients aimed to understand infecting agents, predisposing factors, and outcomes, with a focus on factors affecting mortality. Methods: Data were collected from 39 centers across 16 countries between January 2010 and December 2022, and clinical, radiological, and microbiological findings, along with their impact on mortality, were analyzed. Results: The patients had a mean ± SD age of 46.8 ± 16.3 years, with a male predominance of 71.6%. Common symptoms included headache (77.9%), fever (54.4%), and focal neurological deficits (53.5%). Gram-positive cocci were the predominant pathogens, with Viridans group streptococci identified as the most frequently isolated organisms. All patients received antimicrobial therapy and 71.6% underwent interventional therapies. The 42-day and 180-day survival rates were 91.9% and 86.1%, respectively. Significant predictors of 42-day mortality included intravenous drug addiction (HR: 6.02, 95% CI: 1.38-26.26), malignancy (HR: 3.61, 95% CI: 1.23-10.58), confusion (HR: 2.65, 95% CI: 1.19-5.88), and unidentified bacteria (HR: 4.68, 95% CI: 1.76-12.43). Significant predictors of 180-day mortality included malignancy (HR: 2.70, 95% CI: 1.07-6.81), confusion (HR: 2.14, 95% CI: 1.11-4.15), temporal lobe involvement (HR: 2.10, 95% CI: 1.08-4.08), and unidentified bacteria (HR: 3.02, 95% CI: 1.49-6.15). Conclusion: The risk of death in PBA extends beyond the infection phase, with different factors influencing the 42-day and 180-day mortality rates. Intravenous drug addiction was associated with early mortality, while temporal lobe involvement was associated with late mortality.
Keywords: Intravenous Drug Addiction; Microbiological Findings; Mortality; Primary Brain Abscesses; Temporal Lobe Involvement